Failure analysis and structure optimization of the connecting thread of driving shaft in positive displacement motor - Xiaohua Zhu; Dian Lin; Jianan Li (Advances in Mechanical Engineering, 2016)
Due to high efficiency in helping breaking rocks, positive displacement motor has a widespread application in the field of oil and gas drilling engineering. However, service life of positive displacement motor becomes shorter resulting from failure of the driving shaft thread. The three-dimensional simulation model of driving shaft’s connecting thread has been developed based on the principle of virtual work, Von Mises yield criterion, and contact nonlinear theory. This article has put forward the plan to optimize structure of driving shaft with straight thread based on the design principle of double-shouldered thread; besides, fatigue life of driving shaft with straight thread before and after optimization has been assessed by resorting to the multiaxial fatigue principle and Brown–Miller critical plane rule. In line with research results, mechanical properties of driving shaft with straight thread are superior to those of driving shaft with taper thread. Under the load of axial drill pressure with fluctuation and alternating torque, fatigue life of driving shaft with straight thread after optimization is greatly improved. This article has not only provided basis for optimizing connecting thread of driving shaft but also boasts of high engineering value for improving service life of positive displacement motor.